Aging as a consequence of the adaptation-maladaptation dilemma - Lissek, Thomas (Universitätsbibliothek Heidelberg, 2023)
In aging, the organism is unable to counteract certain harmful influences over its lifetime which leads to progressive dysfunction and eventually death, thus delineating aging as one failed process of adaptation to a set of aging stimuli. A central problem in understanding aging is hence to explain why the organism cannot adapt to these aging stimuli. The adaptation-maladaptation theory of aging proposes that in aging adaptation processes such as adaptive transcription, epigenetic remodeling and metabolic plasticity drive dysfunction themselves over time (maladaptation) and thereby cause aging-related disorders such as cancer and metabolic dysregulation. Molecular mediators of this adaptation-maladaptation dilemma include CREB, Myc and IL-6. The central conundrum of aging is thus that the set of adaptation mechanisms that the body uses to deal with internal and external stressors overlaps with the set of aging stimuli. The only available option for the organism to counteract this maladaptation might be a genetic program to progressively reduce the output of adaptive cascades (e.g. via genomic methylation) which then leads to reduced physiological adaptation capacity and syndromes like frailty, immunosenescence and cognitive decline. The adaptation-maladaptation framework of aging entails that certain biological mechanisms can simultaneously protect against aging as well as drive aging and that aging might have components that are programmed and others that are not programmed. Several known longevity interventions such as exercise and dietary restriction seem to shift the adaptation-maladaptation balance in favor of adaptation and the key to longevity might lie in uncoupling adaptation from maladaptation.